Are digital interventions for smoking cessation in pregnancy effective? A systematic review protocol. Issue 1 (December 2016) - Griffiths, Sarah; Brown, Katherine; Fulton, Emily; Tombor, Ildiko; Naughton, Felix
Abstract Background Behavioural support for smoking cessation in pregnancy can be effective; however, many pregnant women face barriers to seeking support to stop smoking. Some digital interventions have been found to be effective for smoking cessation in the general population and may be effective for supporting cessation in pregnancy due to their flexibility and the potential for personalisation. To date, there is limited evidence of the effectiveness of digital interventions for smoking cessation in pregnancy. This review aims to assess the following: (1) whether digital interventions are effective at promoting smoking cessation among pregnant women; (2) which behaviour change techniques (BCTs) or combinations of BCTs are associated with the effectiveness of digital interventions for smoking cessation in pregnancy; and (3) whether the number of BCTs used is associated with the effectiveness of digital interventions for smoking cessation in pregnancy. Methods This review will include digital interventions delivered largely through computer (PC or laptop), video/DVD, mobile phone (including smartphones) or portable handheld device (e.g. tablet, iPad) and include websites, mobile or tablet applications and SMS text messages. Interventions must be randomised or quasi-randomised controlled trials aimed at women who smoke in pregnancy, with smoking cessation as a measured outcome (preferably the latest available point prevalence smoking status measure taken during pregnancy, biochemically verified if available). Electronic bibliographic databases will be searched to identify suitable studies indexed in the following: Academic Search Complete, ASSIA, CINAHL, The Cochrane Library, EMBASE, Medline, PsycINFO, Scopus, and Web of Science. The search strategy will include key words and database-specific subject headings relating to 'pregnancy' and 'smoking' and synonyms for the terms 'digital' and 'randomised controlled trial'. Where required and where possible, the first and second authors will independently code interventions and control groups for BCTs. If data allows, meta-analyses will be used to assess intervention effectiveness and the effectiveness of BCTs. Discussion This systematic review will provide a detailed synthesis of the effectiveness of current research using digital interventions for smoking cessation in pregnancy, to build on the evidence base and guide the development of future research in this area. Systematic review registration PROSPEROCRD42016036201